2023
DOI: 10.3389/fphar.2023.1173961
|View full text |Cite
|
Sign up to set email alerts
|

The identification of metabolism-related subtypes and potential treatments for idiopathic pulmonary fibrosis

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is caused by aberrant repair because of alveolar epithelial injury and can only be effectively treated with several compounds. Several metabolism-related biomolecular processes were found to be involved in IPF. We aimed to identify IPF subtypes based on metabolism-related pathways and explore potential drugs for each subtype.Methods: Gene profiles and clinical information were obtained from the Gene Expression Omnibus (GEO) database (GSE70867 and GSE93606). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Metabolomics, which focuses on small molecule metabolites such as amino acids (AAs), lipids, fatty acids and carbohydrates, holds great promise for identifying biomarkers for chronic lung diseases due to its high sensitivity, specificity and accuracy. [3][4][5][6] Maintaining metabolic homeostasis is crucial for normal cellular structure and function, as any imbalance can lead to various cell injuries and even cell death, ultimately affecting the integrity of lung function and contributing to the development of lung diseases. Current research is striving to incorporate metabolomics as part of a comprehensive approach for disease diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics, which focuses on small molecule metabolites such as amino acids (AAs), lipids, fatty acids and carbohydrates, holds great promise for identifying biomarkers for chronic lung diseases due to its high sensitivity, specificity and accuracy. [3][4][5][6] Maintaining metabolic homeostasis is crucial for normal cellular structure and function, as any imbalance can lead to various cell injuries and even cell death, ultimately affecting the integrity of lung function and contributing to the development of lung diseases. Current research is striving to incorporate metabolomics as part of a comprehensive approach for disease diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite important advances in therapy for these lung diseases, there remain unmet clinical needs for targeted and highly effective treatment. Metabolomics, which focuses on small molecule metabolites such as amino acids (AAs), lipids, fatty acids and carbohydrates, holds great promise for identifying biomarkers for chronic lung diseases due to its high sensitivity, specificity and accuracy 3–6 . Maintaining metabolic homeostasis is crucial for normal cellular structure and function, as any imbalance can lead to various cell injuries and even cell death, ultimately affecting the integrity of lung function and contributing to the development of lung diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As a gene implicated in metabolism, GPD1L plays a crucial role in regulating energy metabolism and maintaining cellular homeostasis [5,6]. Dysfunction of GPD1L may be critical for the survival of tumor cells that lead to abnormal energy metabolism [7]. Several studies have reported that GPD1L can inhibit the progression of various types of cancer cells, including those found in oropharyngeal cancer, kidney cancer, lung adenocarcinoma, and colorectal cancer [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%